Neuromuscular characteristics of transcranial direct current stimulation over dorsolateral prefrontal cortex in patients with chronic low back pain: a randomized, double-blind, controlled trial protocol - Li, Xin; Liang, Wenzhao; Li, Zhicheng; Li, Shijue; Zu, Yao; Ge, Le; Wang, Chuhuai (Frontiers in Human Neuroscience, 2025)
BackgroundChronic low back pain (cLBP) is a prevalent condition associated with poor rehabilitation outcomes and high recurrence rates. Previous studies suggest that the number, structure, and network patterns of trunk muscle synergy may contribute to this condition. Our previous research mapped the neural representation of cLBP trunk muscles in the primary motor cortex (M1) and identified a disrupted M1-trunk muscle synergy pattern. Recent studies indicate that the dorsolateral prefrontal cortex (DLPFC) has a key role in the internal connectivity of cLBP patients when coping with chronic pain. This study aims to determine whether transcranial direct current stimulation (tDCS) of the DLPFC in cLBP patients can enhance the activity and functional connectivity of M1 and DLPFC, thus improving abnormal trunk muscle synergy.MethodsThis study is a randomized, double-blind, controlled trial. Forty-eight individuals aged 20 to 55 years with cLBP will be randomly assigned to receive either (1) a 3-week DLPFC-tDCS intervention (n = 24) or (2) a 3-week M1-tDCS intervention (n = 24), administered four times per week for a total of 12 sessions. Clinical outcomes will be assessed at baseline, 3 weeks, and 6 and 12 months after randomization. Primary outcomes include pain intensity, disability, and scores on the Hamilton Depression and Hamilton Anxiety scales. Secondary outcomes include surface electromyography characteristics of trunk muscles, oxygenated and deoxygenated hemoglobin concentrations in the M1 and DLPFC, and functional connectivity between these two brain regions. These outcomes will be evaluated before and after the intervention. Effect sizes and a mixed-model repeated measures analysis of variance (2 groups × 4 time points) will be calculated.DiscussionThe results of this trial will clarify the efficacy of DLPFC-tDCS in enhancing M1-DLPFC functional connectivity and improving trunk muscle synergy patterns. These findings will provide a theoretical foundation for developing new therapeutic targets for the treatment of cLBP.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2300078887.